Comparative study on porous media combustion characteristics using different discrete materials - Ayub Ahmed Janvekar; M. Z. Abdullah; Z. A. Ahmad; Aizat Abas; Musavir Bashir; Mazlan Mohamed (2018)
Occurrence of combustion phenomenon in porous media has always excited researchers to develop various shape and size of burner so that maximum utilization of energy can be taken achieved. Here in this experiential work, dual layer micro burner was exclusively built to carry out porous media combustion characteristic with different type of discrete material in reaction zone. Presently, only alumina and zirconia are compared in discrete form, while preheat layer was made of porcelain ceramic material (foam type). Reaction zone was restricted to thickness of 20mm while preheat zone at 10mm. A concept of equivalence ratio was aided since it involves premixed combustion of air and butane as fuel mixture. Additionally, burner was made to run under lean to ultra-lean modes and finest temperature were recorded. Both surface and submerged flame was generated effectively. Maximum temperatures recorded during surface and submerged flame condition was better by installing alumina rather than zirconia there by reaching a value of 631°C and 470°C respectively. Thus maximum thermal efficiency was calculated and found out to be 84%. Finally, emission parameters like NOx and CO where monitored and found out to be well within acceptable limits.